Factors that Influence Student's Decisions in Choosing a Management Study Program at Buana Perjuangan University Karawang (Case Study of Students Class of 2023) - Fajrin, Yeni; Arisandi, Vidya; Sumarni, Neni; Abdilah, Surya Rahmat; Nandini, Imelda Nova (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This research aims to determine the factors influencing students' choice of management study program at Buana Perjuangan University, Karawang. Data was collected by distributing a questionnaire in the form of a Google form to 2023 Management Study Program students via the WhatsApp group, the data collected was 232 respondents. The design used in this research is Confirmatory Factor Analysis and Exploratory, which is a quantitative type of research. The research results were that 5 factors influenced students in choosing a management study program: interest and talent factors, with a variance value of 36.926%. The second is the career opportunity at 8.737%, the third is the study program quality at 7.363%, the fourth is the economy at 5.320%, and the fifth is the support of parents, friends, and the environment at 5.024%. With a total variance, the influence is 63.37% on students' decisions in choosing the Management Study Program. The factors with the highest contribution are interest and talent factors with an eigenvalue of 11.078. This can be a reference for management study programs to provide supportive facilities and infrastructure so students can optimally develop their interests and talents.